EphB2 receptor controls proliferation/migration dichotomy of glioblastoma by interacting with focal adhesion kinase - Wang, Shervin D. (2012)
Glioblastoma multiforme (GBM) are the most frequent and aggressive primary brain tumors in adults. Uncontrolled proliferation and abnormal cell migration are two prominent spatially and temporally disassociated characteristics of GBMs. In this study, we investigated the role of the receptor tyrosine kinase EphB2 in controlling the proliferation/migration dichotomy of GBM. We studied EphB2 gain-of-function and loss-of function in glioblastoma-derived stem-like neurospheres (GBM-SCs), whose in vivo growth pattern closely replicates human GBM. EphB2 expression stimulated GBM neurosphere cell migration and invasion, and inhibited neurosphere cell proliferation in vitro. In parallel, EphB2 silencing increased tumor cell proliferation and decreased tumor cell migration. EphB2 was found to increase tumor cell invasion in vivo using an internally controlled dual-fluorescent xenograft model. Xenografts derived from EphB2 overexpressing GBM neurospheres also showed decreased cellular proliferation. The non-receptor tyrosine kinase focal adhesion kinase (FAK) was found to be co-associated with and highly activated by EphB2 expression and FAK activation facilitated focal adhesion formation, cytoskeleton structure change and cell migration in EphB2-expression GBM neurosphere cells. Taken together, our findings indicate that EphB2 has pro-invasive and anti-proliferative actions in GBM stem-like neurospheres mediated, in part, by interactions between EphB2 receptors and FAK. These novel findings suggest that tumor cell invasion can be therapeutically targeted by inhibiting EphB2 signaling and that optimal anti-tumor responses to EphB2 targeting may require the concurrent use of anti-proliferative agents.